STRATEGI PENDEKATAN PASTORAL TERHADAP PERKAWINAN KEDUA - Jonidius Illu; Nehemia Nome; Riste Tioma Silaen (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
The main problems of writing this article are; first, some couples want to marry for the second time but do not show legal evidence of divorce from the first marriage. Second, they are not preparing for a second marriage through premarital counseling. Third, they are dishonest and open to the failure of the first marriage, so they choose to marry secretly, and certain pastors or churches can accept this. The author would like to explain the pastoral strategy a church pastor carried out in preparing for a second marriage so that it can be accepted in terms of Christian faith, law and culture. The research method used is qualitative research. So it can be concluded that there needs to be a strategy carried out by a pastor in carrying out pastoral care for second marriages so that marriages that will run for a lifetime or are expected to avoid divorce again are guided by a pastoral approach to second marriages. This is necessary to reflect to the world that the church or His people are salt and light so that the name of Jesus Christ is glorified.